Implementasi Program Indonesia Pintar (PIP) Dalam Mendukung Pemerataan Pendidikan di Kota Palangka Raya - Delpin D; Billy Agustino (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The Program Indonesia Pintar (PIP) represents a strategic government initiative designed to expand educational accessibility and foster equity for students from economically disadvantaged backgrounds through the Kartu Indonesia Pintar (KIP). At the local level, the Palangka Raya City Education Office plays a crucial role as a facilitator and supervisor of this program. This study aims to analyze the dynamics of PIP's implementation by the Palangka Raya City Education Office, evaluate its effectiveness in promoting educational equity, and identify the driving and hindering factors encountered in the field. Utilizing a descriptive qualitative approach, data were gathered through literature and documentation studies of scientific journals, government regulations, and official institutional reports. The findings indicate that the distribution of PIP in Palangka Raya City has generated a positive impact by alleviating students' financial burdens and mitigating dropout risks. Nevertheless, the program's efficiency at the local level remains constrained by classic issues such as data inaccuracies in student proposals (inclusion-exclusion errors), banking bureaucracies, delayed disbursements, and a lack of socialization to suburban areas. Continuous refinement of Dapodik data systems, stringent supervision by the Education Office, and enhanced multi-stakeholder coordination are imperative to ensure the optimal acceleration of educational equity in Palangka Raya City.